Energy efficiency of production of livestock products of a small enterprise within the limits of the system of parameters and norms of technological and technical solutions - Marchenko, V.; Trishin, O.; Chyhrynov, E.; Drozdov, S.; Petrash, V.; Tkachov, A.; Ponomareva, V. (Scientific Progress & Innovations, 2023)
Data on the current state of development of cattle breeding of various types of farms in retrospect from 1990 to the present are given. Cow herds, average annual milk yield from one cow, gross milk production in general and by categories of producers are presented. Based on the monitoring and analysis of production and organizational indi-cators of more than 50 farms, including small ones (up to 10 cows), the main elements that characterize them were determined. Accordingly, a version of the technology of tethered keeping of cows with elements of production or-ganization within the parameters is disclosed. The harvesting conditions, the use of fodder crops, the necessary amount of fodder to ensure the given productivity of technological groups are shown. The size of the fodder fund of the farm as a whole, taking into account the insurance reserve, is determined. Also presented is a system for stream-lining the structure of fodder crop sown areas and makes it possible to use land resources more efficiently. Evaluation and modeling of energy efficiency of production were carried out using the example of a pilot project for 20 cows with an annual productivity of 7000 kg to 9000 kg of milk per head. Calculated structure of energy content of products by species ‒ milk, live weight of culled animals, growth of reared animals, obtained offspring. The energy content of excrement and bedding is taken into account. It is calculated that the largest share in the structure of the energy content of products suitable for food belongs to the energy content of produced milk - 86.8–89.4 %, and since it is the most influential factor on the energy efficiency coefficients of the main and general products, the functional dependence of the energy content of products on fat is determined in milk and the relationship between the coeffi-cients of energy content of products and milk fat. The impact of changes in the quality (fat content of culled livestock and animals from which they receive an increase) of other types of products on the energy costs of production is calculated. The established functional dependencies make it possible to form the key elements of interrelationships of the livestock production system, taking into account the specifics of a specific system of parameters, to determine the energy efficiency of technological processes and to effectively influence the use of all types of resources.